2011
DOI: 10.1007/s13355-011-0056-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of the white-spotted longicorn beetle Anoplophora spp. (Coleoptera: Cerambycidae) in Japan detected by mitochondrial DNA sequence

Abstract: Genetic variation of the white-spotted longicorn beetle Anoplophora spp., distributed on the Japanese mainland and the Ryukyu Islands, was examined using nucleotide sequences of mitochondrial DNA. Two fragments, a 1.2-kblong fragment containing portions of the cytochrome oxidase subunit I and II genes and a 1.4-kb-long fragment containing portions of 16S and 12S rDNAs, were sequenced. In phylogenetic analyses based on the sequences, 294 individuals collected at 75 localities were divided into two major groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…Third, a mitochondrial DNA analysis indicated substantial differences between the two longhorn beetles (Muraji et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…Third, a mitochondrial DNA analysis indicated substantial differences between the two longhorn beetles (Muraji et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…They determined that the phylogenetic tree was divided into three major clades and that Anoplophora [A. glabripennis, A. chinensis and Anoplophora lurida (Pascoe, 1857)] and Monochamus [Monochamus alternatus Hope, 1842, Monochamus urussovi (Fisch., 1806 and Monochamus sutor (L., 1758)] were placed in the third lineage. Apart from such molecular studies supporting morphological studies in the Lamiinae, in another study, Muraji et al (2011) determined that the genetic variation of species belonging to the Anoplophora in Japan was identified by mtDNA sequence and the species was split into two main groups. In the same study, they noted that a sample taken in East Honshu was the same as A. chinensis from China.…”
Section: Discussionmentioning
confidence: 99%
“…In DNA extraction studies, leg parts belonging to live or just dead insects were used as described by Muraji et al (2011). DNA was extracted in accordance with the CTAB protocol for invertebrates (Folmer et al, 1994) from three individuals.…”
Section: Dna Extraction and Pcr Amplificationmentioning
confidence: 99%
“…We have used A. malasiaca as the scientific name in this study to follow the Dictionary of Japanese Insect Names (http://konchudb.agr.agr.kyushu-u.ac.jp/dji/), though A. malasiaca is often used as a synonym of A. chinensis (Haack et al 2010). DNA analysis has revealed that A. malasiaca is not necessarily the same as A. chinensis in Japan (Muraji et al 2011).…”
Section: Introductionmentioning
confidence: 99%